Social Well-Being and Adaptive Practices of the Russian Population in the Context of Settlement Differentiation (A Case Study of the Rostov Region) - Sergeevna Panfilova, Yulia; Viktorovich Dyatlov, Alexander; Yurievich Goloborod’ko, Andrey; Vasilyevich Popov, Alexandr; Dmitrievna Skudnova, Tatyana (Opción, 2019)
In the article, the influence of settlement differentiation on social well-being and adaptive practices of the Russian population (using the example of the Rostov region) is considered. Based on the development level of industrial and social infrastructure and local labour market, as well as the breadth of possibilities for increasing human capital within a settlement as criteria for territory differen-tiation, the authors identified four main types of territorial locations: regional centre, district centres, urban-type settlements and rural settlements. Based on the results of empirical measurements, the authors make the case that a type of settlement shapes the social context, which in turn affects the nature of the general public’s social well-being. Analysing the social adaptation model’s relevance to the precarious socio-economic situation (economizing, labour, savings, and self-reliance models), the authors come to the conclusion that the range of possible adaptive practices in the context of socio-economic instability, among other factors, is largely determined by a settle-ment type.